Incomplete contracts and the problem of social harm - Pitchford, Rohan (2000)
We construct a model in which a first mover decides on its location before it knows the identity of the second mover; joint location results in a negative extemality. Contracts are inherently incomplete since the first mover's initial decision cannot be specified. We analyze several kinds of rights, including damages, injunctions, and rights to exclude (arising from covenants or land ownership). There are cases in which allocating any of these basic rights to the first mover-i.e., first-party rights-is dominated by second-party rights, and cases in which the reverse is true. A Coasian result (efficiency regardless of the rights allocation) only holds under a limited set of conditions. As corollaries of a theorem ranking the basic rights regimes, a number of results emerge contradicting conventional wisdom, including the relative inefficiency of concentrated land ownership and the relevance of the generator's identity. We conclude with a mechanism and a new rights regime that each yield the first best in all cases.